2002
DOI: 10.1093/jn/132.6.1598s
|View full text |Cite
|
Sign up to set email alerts
|

Application of Single-Cell Gel Electrophoresis (Comet) Assay for Assessing Levels of DNA Damage in Canine and Feline Leukocytes

Abstract: Increasing evidence suggests involvement of free-radical species in the development of oxidative DNA damage, the consequences of which have been implicated in a number of degenerative disorders associated with the aging process. Here we report the application of a single-cell gel electrophoresis (comet) assay for assessing levels of DNA damage in canine and feline leukocytes. Leukocytes were collected from 24 healthy adult cats and dogs and subjected to DNA damage ex vivo by exposure to a range of hydrogen per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 31 publications
0
36
0
2
Order By: Relevance
“…It has been reported that freezing of lymphocytes does not increase DNA strand breaks as compared to those of freshly isolated lymphocytes, and that fresh and frozen lymphocytes responded almost identically to hydrogen peroxide (Duthie et al, 2002). Visual scoring system used in this study reported to be accurately corresponding to the data that are measured by computer image analysis in human lymphocytes (Collins, 2004), in equine lymphocyte (Marlin et al, 2004) and in canine and feline leukocytes (Heaton et al, 2002). The method used for visual scoring involves classifying comets into four categories on the basis of the perceived length of migration and relative proportion of DNA in the tail.…”
Section: Discussionmentioning
confidence: 56%
“…It has been reported that freezing of lymphocytes does not increase DNA strand breaks as compared to those of freshly isolated lymphocytes, and that fresh and frozen lymphocytes responded almost identically to hydrogen peroxide (Duthie et al, 2002). Visual scoring system used in this study reported to be accurately corresponding to the data that are measured by computer image analysis in human lymphocytes (Collins, 2004), in equine lymphocyte (Marlin et al, 2004) and in canine and feline leukocytes (Heaton et al, 2002). The method used for visual scoring involves classifying comets into four categories on the basis of the perceived length of migration and relative proportion of DNA in the tail.…”
Section: Discussionmentioning
confidence: 56%
“…The comet assay also as known single cell gel electrophoresis (SCGE) was performed and scored with slight modifications according to , Kizilian et al (1999), Tice et al (2000), Saleha Banu et al (2000), Heaton et al (2002), Das et al (2006) and Turkez (2011). The OxiSelect 96-Well Comet Assay kits (Cell Biolabs , San Diego, CA, USA) were used to perform this assay.…”
Section: Scge Assaymentioning
confidence: 99%
“…Then the slides were washed for 5 min with 1 % acetic acid, twice with distilled water, and air-dried. DNA impairment was evaluated by a visual score on a qualitative scale, ranging from 0 (no DNA damage) to 4 (extensive DNA damage, based on the length of the comet tail and on the relative proportion of DNA in the comet head and tail [10]. DNA damage was calculated in units introduced by Collins et al [5].…”
Section: Dna Comet Assaymentioning
confidence: 99%